2008
DOI: 10.1021/jf800975w
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Content of Dietary Fiber and Components Thereof in Wheats in the HEALTHGRAIN Diversity Screen

Abstract: Within the HEALTHGRAIN diversity screening program, the variation in the content of dietary fiber and components thereof in different types of wheat was studied. The wheat types were winter (131 varieties) and spring (20 varieties) wheats (both Triticum aestivum L., also referred to as common wheats), durum wheat (Triticum durum Desf., 10 varieties), spelt wheat (Triticum spelta L., 5 varieties), einkorn wheat (T. monococcum L., 5 varieties), and emmer wheat (Triticum dicoccum Schubler, 5 varieties). Common wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
212
4
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(241 citation statements)
references
References 52 publications
(90 reference statements)
21
212
4
4
Order By: Relevance
“…On the contrary, Iride, Senatore Cappelli and Urria 12 had the lowest values of SDF percentage (10%, 11% and 12%, respectively), showing a preponderance of insoluble fibre components. TDF content was higher than that previously reported by Gebruers et al (2008) for wholemeal durum wheat. However, the difference may be explained by the strong influence that genotype and environmental conditions have on the accumulation of fibre components in wheat grain Shewry et al, 2010).…”
Section: Dietary Fibre Contentcontrasting
confidence: 79%
“…On the contrary, Iride, Senatore Cappelli and Urria 12 had the lowest values of SDF percentage (10%, 11% and 12%, respectively), showing a preponderance of insoluble fibre components. TDF content was higher than that previously reported by Gebruers et al (2008) for wholemeal durum wheat. However, the difference may be explained by the strong influence that genotype and environmental conditions have on the accumulation of fibre components in wheat grain Shewry et al, 2010).…”
Section: Dietary Fibre Contentcontrasting
confidence: 79%
“…(The somewhat lower degree of variability would be expected because the land and climatic conditions vary less in the smaller country, which has fairly homogeneous topography and weather.) Similar variations were observed within species across varieties and growing regions in an extensive study undertaken as part of the European HEALTHGRAIN Project (74,75).…”
Section: Other Key Factors Affecting Nutrients In Whole Grainssupporting
confidence: 71%
“…As mentioned Demirbas (2005) ß-glucan is a major cell wall carbohydrate which is isolated from cereal grains. Grausgruber et al (2004) and Gebruers et al (2008) found that total ß-glucan content varied from 0.3 to 0.4% db in emmer, from 0.23 to 0.90% db in spelt and between 0.25 and 0.48% db in einkorn.…”
Section: Dietary Fibrementioning
confidence: 98%